Dynamics of Nakaseomyces glabratus biofilm formation - E. M. Lenchenko; N. P. Sachivkina; A. V. Liseitsev (Ветеринария сегодня)
Formation of biofilms of microorganisms, including those of Nakaseomyces glabratus, is responsible for the development of local and systemic pathologies in humans and animals. The system of gene expression coordination (quorum sensing) in the representation of signaling molecules allows regulation of the amount and composition of biofilm populations thus expanding the adaptive capacity of microorganisms. In the presence of gingivitis and odontolithiasis clinical signs in dogs, excessive growth of gram-positive yeast microorganisms is a differential sign of the decreased resistance of the digestive system mucous membranes to colonization. Examination of the densitometric and morphometric parameters revealed general patterns of biofilm formation, regardless of the source of Nakaseomyces glabratus isolates. Depending on the time of cultivation of the microorganisms, a gradual increase in the optic density absolute values was established. Intercellular communications were achieved by coaggregation of the heteromorphic structures, which formed clusters with rounded liquid-containing formations detected among them. The population immobilization of the architectonics of the mature three-dimensional biofilm, as consistent with cultivation conditions, was accompanied by the differentiation of numerous cells of different sizes and shapes depending on the stage of the cell cycle. Results of the examination of the general patterns of the heterogeneous micromycete population development are promising for expanding the boundaries of knowledge of the adaptation mechanisms of ubiquitous microorganisms to long-term in vivo and in vitro persistence. Methods for studying morphometric and densitometric indicators avoiding interfering into the natural biofilm architectonics are recommended to optimize the long-term and retrospective mycological studies, as well as to develop effective mycosis treatment and prevention regimens.